THE ROLE OF PERCEPTION IN JONATHAN EDWARDS'S MORAL THOUGHT: The Nature of True Virtue Reconsidered - Choi, Ki Joo (Journal of religious ethics, 2010)
ABSRACT This essay provides an interpretation of Jonathan Edwards's moral thought that calls attention to the motif of perception in his conception of true virtue. The aim is to illumine the extent to which Edwards's virtue ethics can be included in and contribute to prevailing approaches to virtue in contemporary theological ethics. To advance this proposal, this essay attends to the question of moral agency that Edwards's reflections on charity, the new spiritual sense, and religious affections raise. This procedure offers an acute sense of the significance of perception for Edwards's virtue ethics, which in turn allows for a constructive Edwardsean entry into current theological discussions on the narrative character of virtue.